PENGARUH LKPD BERBASIS MODEL PEMBELAJARAN PENINGKATAN KEMAMPUAN BERPIKIR PADA MATERI USAHA, ENERGI, MOMENTUM DAN IMPULS TERHADAP KOMPETENSI FISIKA PESERTA DIDIK KELAS X SMAN 1 PAINAN - Yedho Syahadha; Ratnawulan Ratnawulan; Nurhayati Nurhayati (Universitas Negeri Padang, 2017)
he 2013 curriculum is a curriculum that demands scientific learning. One of the subjects in school that can be done scientifically and support the thinking ability of learners is the subject of physics. However, the reality of the field in the process of physics learning has not fully run in accordance with what is demanded by the 2013 curriculum and not yet support the thinking ability of learners. One of the solutions is to use LKPD-based learning model of thinking skills improvement (MPPKB). The purpose of this research is to investigate the influence of the use of LKPD based on MPPKB on Business, Energy, Momentum and Impuls on the competence of students of class X SMAN 1 Painan.Type of research is Quasi Experiment with postest only control Group Design. The population of the study were students of class X MIA SMAN 1 Painan registered in academic year 2016/2017. Sampling is done by Cluster Random Sampling technique. Research data includes competence of knowledge, attitude, and skill area. The research instruments are final test sheets for knowledge domain competencies, observation sheets for attitude stance competencies, and performance sheets for skills competencies. Technique of data analysis through equality test of two mean with t test statistic at domain of knowledge, attitude, and skill.Based on data analysis conducted, can be presented two results of this study. First, the average score of learners using LKPD based on MPPKB in learning on the knowledge, attitude, and skills of each 83; 83.10; And 86.76. Second, the use of LKPD based on MPPKB gives a significant influence on the physics competence of learners in the realm of knowledge, attitude and skills at the real level of 0.05